Toll-Like Receptors - Aycan Kundakcı; Arash Pirat (Galenos Yayinevi, 2012)
Toll-like receptors (TLR) are a class of proteins that play a key role during the first step of interaction between the pathogens and innate immune system. TLRs help innate immune system to recognize microbial ligands and initiate inflammatory response. Toll-like receptors are also an important link between innate and adaptive immunity through their presence in dendritic cells. The central role of TLR2 and TLR4 in the pathogenesis of sepsis has been clearly demonstrated. As our insight into the mechanisms that induce TLR-associated intracellular pathways increases, the modulation of these pathways turns to be an interesting therapeutic target in septic patients. Recently there has been increasing evidence that TLRs play an important role in commonly encountered non-infectious problems in critically patients such as ischemia reperfusion injury and trauma. It has also been demonstrated that comparing with microbial ligands, heat shock proteins and reactive oxygen species may also activate TLR2 and TLR4 through a different mechanism. In this review, the infectious and non-infectious activation mechanisms of TLRs, their intracellular pathways, and the potential therapeutic approaches that use TLRs or their pathways will be discussed. (Journal of the Turkish Society Intensive Care 2012; 10: 63-73)